INCOME DISTRIBUTION INEQUALITY IN WEST SUMATERA AND THE RELATED FACTORS - Putri Irina Mayang Sari; Sri Mulatsih; Idqan Fahmi (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2014)
Causal relationship between inequality and growth is far from being well understood. In West Sumatera the higher level of growth rate followed by an increasing in Gini ratio or increasing in income inequality. A sharp rise of income inequality has caused discussion about factors affecting inequality. Objectives of this research are to analyze income inequality condition in each Regency/Municipality in West Sumatera and to analyze the factors affecting income inequality. Through the calculation of the Gini ratio, it was found that the highest income distribution inequality in Regency/Municipality level in West Sumatra from 2006 to 2011 are owned by the Mentawai Islands District with an average Gini ratio is 0.311, while the lowest income distribution inequality of the average owned by the Pesisir Selatan District with an average Gini ratio is 0.217. This research is investigated by analyzing a balance panel data with 19 districts from 2006 to 2011. This study found that there are seven variables which can be associated with a movement in income inequality. Income per capita, routine spending for government officials and dummy earthquake have a positive relationship with income distribution inequality.  Meanwhile, industrial sector’s share toward Gross Regional Domestic Products (GRDP), government spending for development program, number of workers in industry and population growth have negative impact.Key words: income distribution, inequality, earthquake, west sumatera